The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1007/s00417-018-3924-x
|View full text |Cite
|
Sign up to set email alerts
|

Features of choroidal naevi on swept source optical coherence tomography angiography and structural reverse flow optical coherence tomography

Abstract: OCTA presents characteristic changes in the choriocapillaris layers in cases of choroidal naevi. The association of naevus substance appearing darker with increasing thickness may offer a novel prognostic clue. En face structural OCT may allow accurate, detailed measurement of lateral dimensions which could be of value in the monitoring of suspicious naevi.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 13 publications
0
12
0
Order By: Relevance
“…In a study of 71 eyes, the visibility of nevus in en face OCTA was 79.5%. Moreover, the thickness greater than 120 μm was associated with darker masses in en face OCTA, which could be interpreted as a prognostic factor [ 18 ] (Fig. 1 ).…”
Section: Melanocytic Lesionsmentioning
confidence: 99%
See 1 more Smart Citation
“…In a study of 71 eyes, the visibility of nevus in en face OCTA was 79.5%. Moreover, the thickness greater than 120 μm was associated with darker masses in en face OCTA, which could be interpreted as a prognostic factor [ 18 ] (Fig. 1 ).…”
Section: Melanocytic Lesionsmentioning
confidence: 99%
“…It is shown that relatively flat nevi do not alter the outer retinal vessels in OCTA; however, errors in automatic segmentation of retinal layers disturb the visualization of the vasculature in the outer retina in thicker tumours [ 18 ].…”
Section: Melanocytic Lesionsmentioning
confidence: 99%
“…Two recent studies revealed successful vascular evaluation of choroidal nevi and melanomas using SS-OCTA. The first study by Ali et al 10 focused on the use of structural reverse flow to identify choroidal nevi. The second study by Pellegrini et al 11 showed the ability of SS-OCTA to identify tumor microvasculature in choroidal melanomas.…”
mentioning
confidence: 99%
“…OCT has improved visibility of the choroid as enhanced depth imaging or swept-source OCT [9][10], autofluorescence scans have confirmed lipofuscin deposition [11] and optical coherence tomography angiography may give information on blood flow. [12] Ultrawide field imaging has been an important addition in this array of imaging modalities because of the ability of capture a wide area of the fundus. In the assessment of intraocular tumours, it has allowed better depiction of the extent of sizable or very peripheral tumours not easily captured with previously available cameras.…”
Section: Discussionmentioning
confidence: 99%